The genus Neotrichia Morton 1905 (Insecta: Trichoptera: Hydroptilidae) in Roraima state, Brazil: New records and description of seven new species - de Liege Gama Neto, Jaime; Passos, Mahedy Araujo Bastos (Zootaxa, 2019)
Seven new species of Neotrichia Morton 1905 from Brazil are described: Neotrichia caboca sp. nov., Neotrichia capitiana sp. nov., Neotrichia cruviana sp. nov., Neotrichia damurida sp. nov., Neotrichia macuxi sp. nov., Neotrichia makunaima sp. nov., and Neotrichia matula sp. nov. Illustrations of male genitalia are provided with each description. New country records for Brazil of two additional species, Neotrichia tauricornis Malicky 1980 and Neotrichia parabullata Harris & Armitage 2015 are also provided.